Online Videoconferencing Products: Update - Douglas Burton; Tim Kitchen (International Review of Research in Open and Distributed Learning, 2011)
Software allowing real-time online video connectivity is rapidly evolving. The ability to connect students, staff, and guest speakers instantaneously carries great benefits for the online distance education classroom. This evaluation report compares four software applications at opposite ends of the cost spectrum: DimDim, Elluminate VCS, TokBox, and Vyew. Their benefits and shortcomings are contrasted, and efficient educational scenarios for them are suggested.